Systematic implications of brain morphology in potamotrygonidae (Chondrichthyes: Myliobatiformes). (23rd November 2015) - Fontenelle, João Pedro; de Carvalho, Marcelo R.
ABSTRACT: The gross brain morphology, brain proportions, and position of cranial nerves in all four genera ( Potamotrygon, Plesiotrygon, Paratrygon, and Heliotrygon ) and 11 of the species of the Neotropical stingray family Potamotrygonidae were studied to provide new characters that may have a bearing on internal potamotrygonid systematics. The brain was also studied in four other stingray (Myliobatiformes) genera ( Hexatrygon, Taeniura, Dasyatis, and Gymnura ) to provide a more inclusive phylogenetic context for the interpretation of features of the brain in potamotrygonids. Our results indicate, based on neuroanatomical characters, that the genera Paratrygon and Heliotrygon are sister groups, as are the genera Potamotrygon and Plesiotrygon, agreeing with previous morphological and molecular phylogenetic studies. Both groups of genera share distinct conditions of the olfactory tracts, telencephalon and its central nuclei, hypophysis and infundibulum, morphology and orientation of the metencephalic corpus cerebelli, orientation of the glossopharyngeal nerve, and overall encephalic proportions. The corpus cerebelli of Paratrygon and Heliotrygon is interpreted as being more similar to the general batoid condition and, given their phylogenetic position highly nested within stingrays, is considered secondarily derived, not plesiomorphically retained. Our observations of the corpus cerebelli of stingrays, including Hexatrygon, corroborate that the general stingray pattern previously advanced by Northcutt is derived among batoids. The morphology of the brain is shown to be a useful source of phylogenetically informative characters at lower hierarchical levels, such as between genera and species, and thus, has significant potential in phylogenetic studies of elasmobranchs. J. Morphol. 277:252–263, 2016. © 2015 Wiley Periodicals, Inc.